A typology of populism: understanding the different forms of populism and their implications. Issue 6 (17th August 2020) - Peters, B. Guy; Pierre, Jon
ABSTRACT: Populism has become one of the most commonly used concepts in contemporary political science, albeit one which is often contested. Most of the discussion of populism, however, has focused on elections and political party systems. We argue that populist politics can be seen in a number of other dimensions of governance. We develop a typology of populist practices that appear in both democratic and non-democratic political systems, and discuss their relationships to governance. This article helps to clarify the nature of contemporary populism and its place in politics.